Neurodynamical and Social-psychological Features of Adaptation of Winterers - O.A. Miroshnichenko (Ukrainian Antarctic Journal, 2015)
ln the article the results of researches of neurodinamical and social-psychological features of adaptation of the Ukrainian winterers are presented to the vital functions in the conditions of Antarctic Region оn the example of one of the last expeditions оn the Ukrainian Antarctic station «Academician Vernadskiy».